Novel Polymer Electrolyte Nano-Composite Membranes for Fuel Cell Applications - Zarrin, Hadis (University of Waterloo, 2015)
Fuel cells are electrochemical devices which have been established to lead in the transition to clean energy technology and will become the energy efficient power source of the future. Among all the fuel cell systems, anion exchange membrane fuel cells (AEMFCs) and solid polymer electrolyte membrane fuel cells (PEMFCs) are qualified of achieving high power densities (>l W cm-2) that is required for many applications. Mainly, operation of AEMFCs and PEMFCs at higher temperatures (100-130 °C) would considerably enhance their kinetic performance over the current lower temperature operation technologies. However, due to the type of materials used in each fuel cell there is an associated set of challenges including cost and lifetime which require innovative engineering solutions. One of the important challenges is the fabrication of a cost effective solid electrolyte with high efficiency and durability for both PEMFCs and AEMFCs. Concerning PEMFCs, the state of the art perfluorosulfonic acid (PFSA) membrane (Dupont Nafion®) has high ionic conductivity and good mechanical and chemical stability. However, its high performance and durability is limited to the operational conditions (e.g., temperature, humidity, and pH). In the case of AEMFCs, the dilemma between high ionic conductivity and physicochemical stability for membranes is an important issue, i.e., maximizing one will minimize the other. Thus, for both PEMFCs and AEMFCs, there is a desire to develop a solid electrolyte material capable of maintaining both ion-conductivity and durability at the same time for various operational conditions, especially elevated temperature conditions. The main goal of this research project has been the design and fabrication of novel nano-composite electrolyte membranes that fulfills all the aforementioned requirements for a cost effective solid electrolyte membrane in both PEMFCs and AEMFCs. To accomplish this, different approaches have been effectively integrated and improved by understanding and combination of organic chemistry, electrochemistry, chemical engineering and nano-materials science. Hygroscopic nano-fillers made of titanium oxide nanotubes (TiO2-NT) or graphene oxide (GO) nanosheets were first functionalized with highly ion-conductive groups, and then composed with the commercial membrane or another type of polymeric backbone. The latter was morphologically modified to favor higher electrolyte and water absorption capacity. Combining the benefits of a nano-filler with a morphologically modified polymer electrolyte effectively led to the development of a highly ion-conductive, water-retentive, and durable electrolyte membrane. Electrochemical, thermal, physical and chemical properties of proposed membranes were tested, analyzed and reported by various characterization methods. For PEMFC applications, the developed nano-composite PFSA membranes demonstrated significant ion conductivity and single fuel cell performance improvement (~4 times) over commercial PEM at the humidity of 30 % and temperature of 120 °C. For AEMFCs, the selected nano-filler (e.g., GO) composed with morphologically modified polymer (e.g., porous polybenzimidazole) notably increased both performance and durability of AEMs in harsh alkaline conditions. This work offered promising solid electrolyte replacements synthesized by simple and cost effective techniques, able to meet the fuel cell market demands.
Keywords: Fuel Cells; Nano-composite Membranes; Polymer Electrolyte; Ion Conductivity; Chemical Engineering